Corporate Governance Transformation in Transition Economies: Evidence from Bulgaria - Evgeni Peev (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
The paper presents study of corporate governance evolution in Bulgaria and its convergence to EU structures. The author discusses the traditional approach to separation of ownership and control in transition economies and modern ideas about the need for changing corporate governance paradigm. The study analyses main ownership and control structures in the Bulgarian industry and specific property-rights structures in corporatized state-owned firms, privatized firms and established de novo private enterprises. The research reveals the main constraints on corporate governance convergence to European structures in Bulgaria as the emerging enterprise sector duality and inefficient property-rights structures based on the state-owned firms transformation. The study analyses different paths for corporate governance and country development in the short run.
Keywords: 330; Corporate Governance; Eigentümerstruktur; Privatwirtschaft; Öffentliches Unternehmen; Übergangswirtschaft; Bulgarien